Focus on patient perspectives in climate action policies for healthcare. A German survey analysis on what patients are willing to do - Scholz, Florian; Börner, Nikolaus; Schust, Sophie Anne; Schardey, Josefine; Kühn, Florian; Renz, Bernhard; Angele, Martin; Werner, Jens; Guba, Markus; Jacob, Sven (Frontiers in Public Health, 2024)
The healthcare sector, while focused on improving health, paradoxically contributes to approximately 4.9% of global carbon emissions. Despite rising public concern about climate change, few studies have explored patients' awareness of the environmental impact of healthcare. This study aims to assess patients' perspectives on climate change and healthcare sustainability. A cross-sectional survey was conducted at Ludwig-Maximilians-University (LMU) Hospital in Munich, Germany, using QR codes to invite patients to participate in a voluntary, anonymous online survey. The survey collected demographic data and explored patients' environmental awareness, attitudes towards climate-friendly practices, and willingness to support sustainable initiatives. Among 399 patients who completed the survey (87% completion rate), 92.3% were aware of climate change, and 82.7% prioritized climate-friendly practices in their personal lives. However, 55.9% were unaware of healthcare's contribution to carbon emissions, and only 18.3% knew about hospitals' climate impact. Despite this, 88.2% supported environmentally friendly initiatives in hospitals, and 86.5% were willing to accept sustainable alternatives, provided they maintained care quality. A majority (63.2%) supported a system displaying the carbon footprint of medical procedures, with 54.4% indicating it would influence their treatment choices. Similarly, 62.2% wanted to know the environmental impact of medications, and 65% said it would affect their choices. Notably, 66.2% were willing to support sustainability through shorter hospital stays and follow-up visits, while 35.8% were open to paying a CO2 compensation fee. However, 81% were unwilling to pay higher insurance premiums. Regression analysis found older age and having children were positively associated with environmental awareness, while gender, education, relationship status, and illness severity had no significant effect. The findings reveal a gap between patients' awareness and knowledge of healthcare’s environmental impact and highlight the need for policy changes, education, and innovation to promote sustainable healthcare without compromising care quality.